Al-Ta’lif Al-‘Araby fi Wilayati Nashrawy: Injazat wa Tahaddiyat - Abdulazeez Salman Alyaqooty (Lembaga Penelitian dan Pengabdian kepada Masyarakat(LPPM), STAI PUI Majalengka, 2026)
The language of ??d in Nasarawa State, North-Central Nigeria, continues to maintain its status as one of the global languages. Within its embrace flourishes Arab culture, whose elements are not fully realized except through the cultivation of human intellect, the service of religion, the preservation of traditions, the vessel of customs, and communicative exchange. Writing in Arabic—despite the diversity of its purposes, genres, and stylistic approaches—nourishes the mind, enlightens the conscience, and guides toward the straight path. Through it are reflected the events and occurrences of the society in which such writing is produced, thereby achieving a balance with the cultural outputs of that environment in which the author lives. Moreover, literary production serves society through factors that facilitate the availability of writers and foster creativity. This article seeks to respond to Arab intellectuals by encouraging literary production in Nasarawa State. Through these literary movements, it explores the extent to which the Arabic language meets the needs of the people of Nasarawa State. Undoubtedly and without the slightest doubt, this leads us to recognize certain achievements in Nasarawa State, as well as the challenges facing contemporary Arabic literary production there. The methodology adopted in this study is descriptive, analytical-inductive, and historical. Writing is a skill sharpened by experience and developed through courage, by which the creative individual lives on among the ranks of the immortal.